Is human bone matrix a sufficient augmentation method revising loosened pedicle screws in osteoporotic bone? – A biomechanical evaluation of primary stability. (March 2023) - Egenolf, Philipp; Harland, Arne; Weber, Maximilian; Prescher, Andreas; Bratke, Grischa; Eysel, Peer; Scheyerer, Max Joseph; Lenz, Maximilian
Abstract: Introduction: Despite good screw anchorage and safe screw trajectory, screw loosening occurs in several cases, especially in osteoporotic individuals. The aim of this biomechanical analysis was to evaluate the primary stability of revision screw placement in individuals with reduced bone quality. Therefore, revision via enlarged diameter screws was compared to the use of human bone matrix as augmentation to improve the bone stock and screw coverage. Methods: 11 lumbar vertebral bodies from cadaveric specimens with a mean age of 85.7 years (± 12.0 years) at death were used. 6.5 mm diameter pedicle screws were inserted in both pedicles and hereafter loosened using a fatigue protocol. Screws were revised inserting a larger diameter screw (8.5 mm) in one pedicle and a same diameter screw with human bone matrix augmentation in the other pedicle. The previous loosening protocol was then reapplied, comparing maximum load and cycles to failure between both revision techniques. Insertional torque was continuously measured during insertion of both revision screws. Findings: The number of cycles and the maximum load until failure were significantly greater in enlarged diameter screws than in augmented screws. The enlarged screws' insertional torque was also significantly higher than of the augmented screws. Interpretation: Human bone matrix augmentation does not reach the same ad-hoc fixation strength as enlarging the screw's diameter by 2 mm and is therefore biomechanically inferior. Regarding the immediate stability, a thicker screw should therefore be prioritised. Highlights: Ad-hoc stability of human bone matrix augmentation is inferior to enlarging the screw diameter. Maximum insertional torque of bone augmented screws is inferior to thicker screws. Insertional torque over the first half of the screw's thread did not differ between revision groups. Insertional torque over the second half of the screw's thread was greater in thicker screws.